Genes involved in DMSO-mediated yield increase of entomopathogenic nematodes - Xingxin Liu; Zhongchen Rao; Richou Han; Linhong Jin; Li Cao (Scientific Reports)
Abstract Entomopathogenic nematodes (EPNs) associated with their symbiotic bacteria can effectively kill insect pests, in agriculture, forestry and floriculture. Industrial-scale production techniques for EPNs have been established, including solid and liquid monoculture systems. It is found that supplement of 0.01% dimethyl sulfoxide (DMSO) to the culture medium significantly enhances the recovery and infective juvenile yield of these nematodes. However, the specific nematode genes responding to DMSO is not yet clear. This study identified differentially expressed genes and associated enriched pathways by analyzing the transcriptomic response of Heterorhabditis bacteriophora H06 in the liquid medium containing 0.01% DMSO, and validated the function of the selected genes using RNA interference (RNAi). 11 upregulated and 295 downregulated genes were detected in the hermaphrodites of H. bacteriophora H06 at 3 days beforee egg formation, following DMSO treatment. The biological processes involved included regulation of biological processes, metabolism, binding, signal transduction, post-transcriptional modifications, metabolism, and protein folding. By using RNAi, knockdown of three genes, Hint module, PAN domain protein, and Dpy-13, significantly regulated the egg load (at least a 17% increase in eggs per hermaphroditic adult) and the yield of infective juveniles (at least a 48% increase), in an optimized 96-well plates containing the medium with 1.6% nutrient broth, 1% corn oil and 1.2% agar, without DMSO. qRT-PCR results confirmed that the expression levels of the knockdown genes decreased significantly, compared to the control. These results demonstrate that DMSO regulates nematode gravidity by suppressing at least three selected genes, thereby enhancing IJ yield, providing molecular cues for understanding how DMSO regulates the EPN yield, and a new technology for enhancing nematode commercial production.